Effects of extracerebral dopamine on salsolinol‐ or thyrotropin‐releasing hormone‐induced prolactin (PRL) secretion in goats. (20th March 2016) - Inaba, Yuki; Kato, Yuki; Itou, Azumi; Chiba, Aoi; Sawai, Ken; Fülöp, Ferenc; Nagy, György Miklos; Hashizume, Tsutomu
Abstract: The aim of the present study was to clarify the effect of extracerebral dopamine (DA) on salsolinol (SAL)‐induced prolactin (PRL) secretion in goats. An intravenous injection of SAL or thyrotropin‐releasing hormone (TRH) was given to female goats before and after treatment with an extracerebral DA receptor antagonist, domperidone (DOM), and the PRL‐releasing response to SAL was compared with that to TRH. DOM alone increased plasma PRL concentrations and the PRL‐releasing response to DOM alone was greater than that to either SAL alone or TRH alone. The PRL‐releasing response to DOM plus SAL was similar to that to DOM alone, and no additive effect of DOM and SAL on the secretion of PRL was observed. In contrast, the PRL‐releasing response to DOM plus TRH was greater than that to either TRH alone or DOM alone and DOM synergistically increased TRH‐induced PRL secretion. The present results demonstrate that the mechanism involved in PRL secretion by SAL differs from that by TRH, and suggest that the extracerebral DA might be associated in part with the modulation of SAL‐induced PRL secretion in goats.